Evaluation of thermosetting resin curing using a tilted fiber Bragg grating. (July 2022) - Hirota, Itsuhiko; Takeda, Shin-ichi; Ogasawara, Toshio
Abstract: The strain, temperature and refractive index of a material can be evaluated from the Bragg and cladding modes in the transmission spectra of tilted fiber Bragg gratings (TFBGs). The strain and refractive index of thermosetting resin are evaluated from the changes in these indicators. Changing the mechanical strain of the TFBG (thus varying the refractive index from 1.56 to 1.64) negligibly changed the transmission spectrum, suggesting that strain and refractive index can be simultaneously measured. The curing process of the epoxy adhesive film was monitored by measuring the film's refractive index through the TFBG. The relationship between the refractive index and curing degree was quantified using the Kamal model based on isothermal curing kinetics. When measuring the degree of resin curing, the TFGB-based method performed at least as well as Fresnel reflection-based fiber-optic sensors, demonstrating its usefulness in monitoring the strain and curing degree of thermosetting resin-based materials.